2006
DOI: 10.1073/pnas.0603584103
|View full text |Cite
|
Sign up to set email alerts
|

Microstimulation of the somatosensory cortex can substitute for vibrissa stimulation during Pavlovian conditioning

Abstract: The primary somatosensory cortex (S1) contains a map representation of the body surface. We hypothesized that S1 stimulation can successfully substitute for (or be substituted by) direct stimulation of skin receptors. We prepared rabbits for evoking eyelid conditioned responses (CRs) using a trace ''shock-air puff'' paradigm. In a first series of experiments, animals received a conditioned stimulus (CS, a train of electrical pulses) in the whisker pad or in the S1 areas for vibrissae or for the hind limb. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…A previous study indicated that specific areas of the somatosensory cortex are activated during this type of associative learning, depending on the skin site of the CS presentation (17). As in that study, we used a train of pulses (100 ms, 200 Hz) presented to the whisker pad as CS, followed 250 ms later by an air puff presented to the ipsilateral cornea as an unconditioned stimulus (US).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that specific areas of the somatosensory cortex are activated during this type of associative learning, depending on the skin site of the CS presentation (17). As in that study, we used a train of pulses (100 ms, 200 Hz) presented to the whisker pad as CS, followed 250 ms later by an air puff presented to the ipsilateral cornea as an unconditioned stimulus (US).…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, beyond the local encoding of stimulus features, learning plays an important role, as by learning, meaning is attributed to the electrical stimuli (Scheich and Breindl, 2002;Bradley et al, 2005;Fernández et al, 2005;Leal-Campanario et al, 2006). When animals learn to discriminate or categorize natural, e.g., visual, auditory, or somatosensory stimuli, large-scale stimulus-specific patterns emerge from the ongoing activity of sensory cortex as has been demonstrated by recording electrocorticograms (ECoGs) at high spatial resolution (Barrie et al, 1996;Freeman, 2000;Ohl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In animal models it has been shown that electrically evoked percepts vary in accordance with the location of the stimulation site within retinotopic (Bradley et al, 2005), tonotopic (Scheich and Breindl, 2002;Otto et al, 2005), and somatotopic (Leal-Campanario et al, 2006;Fitzsimmons et al, 2007) map representations. Several studies have specifically demonstrated that psychophysical properties of electrically evoked percepts can be linked to the representational topographies of cortical maps at the stimulation site (Romo et al, 2000;Bartlett et al, 2005), in some cases even to tuning properties of small sets of directly excited neurons located within one or a few cortical columns (Tehovnik et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical microstimulation can establish causal links between the activity of groups of neurons and perceptual and cognitive functions [1][2][3][4][5][6] . However, the number and identities of neurons microstimulated, as well as the number of action potentials evoked, are difficult to ascertain 7,8 .…”
Section: Introductionmentioning
confidence: 99%